Peningkatan Daya Saing UMKM di Kota Pontianak melalui Pelatihan Sertifikasi Halal Self-Declare - Supriaman, Supriaman; Memet Agustiar; Faishol Luthfi; M. Iman Taufik; Diah Arminingsih (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Training on Submitting Halal Certification Through the Self-Declare Mechanism for Micro, Small and Medium Enterprises (MSMEs) in Pontianak City aims to increase the understanding and ability of MSME actors in the halal certification process, especially with the self-declare method. This training was given to participants totaling 30 representatives of MSMEs in Pontianak City. This training was carried out in several stages, including the delivery of material on halal certification regulations, procedures for filling out the required documents, selecting raw materials that comply with halal standards, and assistance in the certification registration process. The results of the training showed that the majority of participants, namely MSME players in Pontianak City, experienced a significant increase in understanding of the requirements and procedures for applying for halal certification. In addition, participants were also given simulations of filling out forms and practical assistance that helped speed up the process of applying for certification. The post-training evaluation showed an increase in the participants' ability to compile the required administrative documents, as well as in ensuring that the entire production process meets halal standards. As a result, some participants successfully applied for halal certification through the self-declare mechanism more confidently and effectively. This training is expected to increase the competitiveness of MSMEs and open up opportunities for expansion of the halal product market at the national and international levels.